1994
DOI: 10.1116/1.579197
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam effects on (CH2)17 self-assembled monolayer SiO2/Si specimens

Abstract: This paper examines the damage created by an electron beam on layered specimens consisting of a (CH2)17 self-assembled monolayer (SAM) deposited on an oxidized Si wafer. Beam effects on both the SAM and substrate were observed. X-ray photoelectron spectroscopy (XPS) measurements indicate that less than 20% of the carbon from the film is lost during the beam damage, ion analysis shows hydrogen emission from the films, and residual gas analysis suggest loss of some CHx (x=2–4) molecules. Consistent with the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…By incorporating the observed water contact angle data for the irradiated surfaces in eq 6, together with the constraint that f 1 + f 2 = 1, we determined the values of the fractional coverages of hydrophobic and hydrophilic groups, and the calculated surface chemical compositions are given in Figure as a function of the e-beam dose. The observed decrease in the fraction of the combined hydrophobic CH 2 and CH 3 groups can be attributed to the loss of hydrogen atoms during the process. , Hexadecane contact angles were also measured for these surfaces, and in all cases e-beam irradiation results in a drop from the initial values of ∼43° to nearly zero, equivalent to complete wetting. Since the initial surfaces exhibit a pure CH 3 character, while pure CH 2 surfaces, e .…”
Section: Resultsmentioning
confidence: 87%
“…By incorporating the observed water contact angle data for the irradiated surfaces in eq 6, together with the constraint that f 1 + f 2 = 1, we determined the values of the fractional coverages of hydrophobic and hydrophilic groups, and the calculated surface chemical compositions are given in Figure as a function of the e-beam dose. The observed decrease in the fraction of the combined hydrophobic CH 2 and CH 3 groups can be attributed to the loss of hydrogen atoms during the process. , Hexadecane contact angles were also measured for these surfaces, and in all cases e-beam irradiation results in a drop from the initial values of ∼43° to nearly zero, equivalent to complete wetting. Since the initial surfaces exhibit a pure CH 3 character, while pure CH 2 surfaces, e .…”
Section: Resultsmentioning
confidence: 87%
“…Step in potential Applied field Contamination layer our earlier work 11 we observed that electron radiation could shift the oxidized Si peak in a thin SiO 2 without broadening peaks from that layer. Because damage-facilitated charge accumulation at the Si/SiO 2 interface was well established, the data were readily understood in terms of the potential shift of the oxide layer after electron beam exposure.…”
Section: Charge Build-upmentioning
confidence: 94%
“…Among these approaches, electron-beam lithography has attracted special attention over the past decade because of the flexibility of this technique and the improved understanding of the phenomena occurring at irradiation of ultrathin organic films with ionizing radiation. The interaction of electron and X-ray beams with different SAMs has been reported in numerous papers and reviewed recently by Zharnikov and Grunze . The response of SAMs to low-energy electrons (10−300 eV) and soft X-rays (100−1500 eV) is similar, because the irradiation-induced modification in the latter case is predominately caused by photo- and secondary electrons .…”
Section: Introductionmentioning
confidence: 91%